Aspek Religiositas Masyarakat Peziarah Makam Shaykh Abdul Muhyi Pamijahan Tasikmalaya - Chaer, Moh. Toriqul (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
Pamijahan as the conduct of the pilgrimage is a phenomen that deserve to be the field of research. Because in that place there are various of human activities and different cultures, beliefs and expectations of the cultural struggle that became a cultural pilgrimage. Pamijahan a mystical village that has a value that is believed to give karÃ¢mah and blessing for the visitors. Blessing is obtained from the pilgrimage performed at the tomb of Shaykh Abdul Muhyi and other tombs at the site. Confidence Pamijahan pilgrims believe that the shrine is the tomb of Shaykh Abdul Muhyi who are considered sacred by many struggles and sacrifices for the religion. Abdul Muhyi struggle to spread Islam and coupled with the value sufistik satariah orders which he got from his teacher. To analyze the motives and goals of pilgrimage Friday Pamijahan author tries to communicate with the theory Tallcot Parsons, the adaptation, goal, integration and latency. The result is there are different motives inter-pilgrims at the funeral Pamijahan. Motifs that can be concluded is the intent or purpose contained in the implementation of the pilgrimage, usually intent was inspired by science or deeds that practiced by the pilgrims, besides other requests.